2001
DOI: 10.1002/etc.5620200904
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hydroxylamino‐dinitroso‐1,3,5‐triazine as a transient intermediate formed during the anaerobic biodegradation of hexahydro‐1,3,5‐trinitro‐1,3,5‐triazine

Abstract: The metabolic fate of hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX) in a mixed culture incubated under methanogenic conditions was studied. Analysis by high-performance liquid chromatography (HPLC) confirmed the loss of RDX and the formation of mono-, di-, and trinitroso-RDX as transient biodegradation intermediates. An additional peak observed in the HPLC chromatograms was identified by liquid chromatography-mass spectrometry as hydroxylamino-dinitroso-1,3,5-triazine. This is the first report identifying hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…The HPLC-2 method was not run with formate to verify this notion. However, other previously reported RDX degradation products such as hydroxylamino metabolites (Adrian & Chow 2001), methylenedinitramine and bis(hydroxymethyl)nitramine (Figure 1) (Hawari et al 2000;Oh et al 2001), are relatively short lived (Adrian & Chow 2001;Bhushan et al 2002) and are unlikely to persist as long as the unidentified metabolites did in this experiment (Figure 3). Similarly, no metabolites were identified using an Agilent 1100 series liquid chromatograph/mass spectrometer, presumably due to lack of sensitivity in full scan mode.…”
Section: Degradation Of 14 C-rdx Under Autotrophic Conditionsmentioning
confidence: 52%
See 1 more Smart Citation
“…The HPLC-2 method was not run with formate to verify this notion. However, other previously reported RDX degradation products such as hydroxylamino metabolites (Adrian & Chow 2001), methylenedinitramine and bis(hydroxymethyl)nitramine (Figure 1) (Hawari et al 2000;Oh et al 2001), are relatively short lived (Adrian & Chow 2001;Bhushan et al 2002) and are unlikely to persist as long as the unidentified metabolites did in this experiment (Figure 3). Similarly, no metabolites were identified using an Agilent 1100 series liquid chromatograph/mass spectrometer, presumably due to lack of sensitivity in full scan mode.…”
Section: Degradation Of 14 C-rdx Under Autotrophic Conditionsmentioning
confidence: 52%
“…Attempts to identify the radiolabeled byproduct(s) after 111 days of incubation were unsuccessful. Several potential RDX metabolites, that have been reported by others (e.g., Adrian & Chow 2001;Hawari et al 2000Hawari et al , 2001McCormick et al 1981;Oh et al 2001;Zhao et al 2003a, b) were not detected using the HPLC-1 or HPLC-RAD analysis methods used for this research. For example, Zhao et al (2003a) showed C. bifermentans HAW-1 transformed RDX transiently to MNX, DNX, and TNX, which were further transformed to methanol, formaldehyde, carbon dioxide, and nitrous oxide.…”
Section: Degradation Of 14 C-rdx Under Autotrophic Conditionsmentioning
confidence: 81%
“…One important characteristic of these bacteria is that they reduce the N-NO 2 groups to N-NO using a type I nitroreductase [2][3][4][5]. These biodegradation metabolites of RDX have been observed in laboratory studies [2][3][4][5], suggesting that MNX, DNX, and TNX may also be produced via bacterial degradation in the natural environment and co-exist in water and soils where RDX occurs. This hypothesis was strengthened by observations of Beller and Tiemeier [6].…”
Section: Introductionmentioning
confidence: 92%
“…Various military and civil activities in certain areas have resulted in the contamination of soil and water with RDX [1]. Under anaerobic conditions, some bacteria can sequentially reduce the N-NO 2 groups on RDX to the corresponding N-NO, ultimately producing (sequentially) hexahydro-1-nitroso-3,5-dinitro-1,3,5-triazine (MNX), hexahydro-1,3-dinitroso-5-nitro-1,3,5-triazine (DNX), and hexahydro-1,3,5-trinitroso-1,3,5-triazine (TNX) [2][3][4] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…RDX is an oxidized pollutant that can be biodegraded under anaerobic conditions [1][2][3][4][5][6][7]. Anaerobic degradation of RDX with zero-valent iron (ZVI) under both abiotic and biotic conditions has been described previously [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%